Labor Market Distortions, Rural-Urban Inequality, and the Opening of China's Economy - Zhai, Fan (The World Bank, 2004)
Hertel and Zhai evaluate the impact of two key factor market distortions in China on rural-urban inequality and income distribution. They find that creation of a fully functioning land market has a significant impact on rural-urban inequality. This reform permits agricultural households to focus solely on the differential between farm and nonfarm returns to labor in determining whether to work on or off-farm. This gives rise to an additional 10 million people moving out of agriculture by 2007 and lends a significant boost to the incomes of those remaining in agriculture. This off-farm migration also contributes to a significant rise in rural-urban migration, thereby lowering urban wages, particularly for unskilled workers. As a consequence, rural-urban inequality declines significantly. The authors find that reform of the Hukou system has the most significant impact on aggregate economic activity, as well as income distribution. Whereas the land market reform primarily benefits the agricultural households, this reform's primary beneficiaries are the rural households currently sending temporary migrants to the city. By reducing the implicit tax on temporary migrants, Hukou reform boosts their welfare and contributes to increased rural-urban migration. The combined effect of both factor market reforms is to reduce the urban-rural income ratio dramatically, from 2.59 in 2007 under the authors' baseline scenario to 2.27. When viewed as a combined policy package, along with WTO accession, rather than increasing inequality in China, the combined impact of product and factor market reforms significantly reduces rural-urban income inequality. This is an important outcome in an economy currently experiencing historic levels of rural-urban inequality. This paper—a product of the Trade Team, Development Research Group—is part of a larger effort in the group to evaluate the poverty impacts of trade policy reforms.